Perception of UPV-CM students regarding the collection of student fees - Ibot, Carl John.; Inocencio, Rolan John.; Limogmog, Vincent John.; Montoya, Kevin; Otayde, Heidebert Paul. (2007)
This study aimed to know the perception of UPV students on the fees imposed by their respective organizations as well as the cause. It also aimed to determine if (1) socio-economic factors such as year level, academic organization, position, weekly allowance, scholarship, monthly family income, people who support them and source of payment affect their perception (2) amount, modes of imposition and modes of payment influence their perception (3) types of fees such as academic organizations and CMSC fees affect their perception on the fees. This research study utilized questionnaire made by the researchers themselves. There were 260 respondents: from first, second, third and fourth year, the data gathered were subjected to computer process statistics, for descriptive analysis, frequency count used were the mean, chi-square at 0.05 ;evel of significant difference and Analysis of Variance (ANOVA) were employed for the inferential part. All the statistical computations were determined using the Statistical Package for Social Science (SPSS). The result of the study showed that some of the personal and organizational variables significantly affect some of the student fees.
Research Paper (BA 199-Business Research) -- [Iloilo City : UPV-CM, March 2007.